Hepcidin in Iron Management in CKD Patients on Haemodialysis: A Translational and Clinical Review of Mechanisms, Evidence, and Implementation Barriers - Sunita Pawar; Jisha Annie Geevarghese (Saudi Journal of Kidney Diseases and Transplantation, 2026)
Abstract Iron dysregulation is common in haemodialysis patients with Chronic Kidney Disease (CKD), which significantly increases anaemia and makes therapeutic management more challenging. The master regulator of systemic iron homoeostasis, has emerged as a promising biomarker and potential therapeutic target for optimising iron therapy in this population. This comprehensive narrative review synthesises current evidence on hepcidin’s role in iron management in haemodialysis patients with CKD, examining its diagnostic and prognostic value, its pathophysiological interactions with inflammation and erythropoiesis, and the obstacles to its integration into standard clinical practice. This narrative review is based on a structured literature search of PubMed, Scopus, and Google Scholar (inception to March 2026); eligible English language studies on hepcidin in CKD and haemodialysis were selected through screening and full-text review and synthesised qualitatively. The review further evaluates the cost-effectiveness of hepcidin testing versus standard iron markers from a healthcare system perspective. Key barriers including assay non-standardisation, the absence of validated clinical thresholds, and the lack of reimbursement pathways, are critically appraised alongside emerging evidence supporting hepcidin-guided anaemia management.